BENTUK-BENTUK STRATEGI AMBUSH MARKETING YANG DIJALANKAN OLEH PIHAK SPONSOR PADA KEJUARAAN DJARUM INDONESIA OPEN - Ygnasius Dio Nanda Permai (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
The role of sport sponsorship as the main option in the marketingcommunication has become a very vital part in funding various kindactivities such as sports, music, soni cultural and social activities.Ambush marketing related to sport, where a company which is notan official sponsor of the event (official partner) conduct a businessthat includes their names, products, and services to a sporting eventor kopetisi with a marketing strategy that is "unique". The purposeof this study was to determine the forms ambush marketingstrategies taken by the sponsor in the Djarum Indonesia OpenChampionship and to determine consumer response to the DjarumIndonesia Open championship against forms of Ambush Marketingstrategy. Results of the study that the shapes strategy AmbushMarketing in run Party Links Championship Djarum IndonesiaOpen, among others: the first one that is, forms of strategiesAmbush marketing is run by the Party Links Championship DjarumIndonesia Open is: Sponsor media coverage of the event orambusher become sponsors of the various media that includeelements of an event, usually by creating events in hot spots aroundthe event took place, a sponsor from the event and performexploitation campaign aggressively, making sponsorship linkedwith the contribution of sports stars as well as engage inAdvertising, which coincided with sposnsor event. Secondly, theconsumer response is part of consumer behavior at thechampionships Djarum Indonesia Open can be shown in willingnessto recommend the brand or ready in recommending the brand toothers, willingness to pay a price premium for the brand, namelythe decision of use of the brand is based on the price offered priceitself is inseparable from the values and benefits that includesproducts or services offered, as well as willingness to accept brandextensions that decition in using an existing brand belonging haslaunched a new product.